Tapping into the Internet as an Acoustical/Musical Medium. - Chafe, Chris (Contemporary Music Review, 2009)
Network audio technology transforms advanced networks into a new kind of sound propagation medium, with its own properties compared to air, water, or solids. Three areas of research are described: 1) methods for using your ears for monitoring quality-of-service (QoS) of networks supporting high-quality, real-time, interactive, bidirectional flows; 2) new musical practices being made in the medium; and 3) a discussion of human factors affected by some unique acoustical properties of the medium.